Description of credit legislation and its defects - Білько, Олександр Павлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The norms of current legislation of Ukraine that is regulate credit relations are analysed in the article, and also the ways of improvement of national legislation in the field of crediting are offered.